A New Species of the Genus Periglischrus (Acari: Spinturnicidae) on Leptonycteris nivalis (Chiroptera: Phyllostomidae) From Mexico, Including a Key to Species of the vargasi Species Group. Issue 1 (19th October 2022) - Morales-Malacara, Juan B; López-Ortega, Gerardo
Abstract: Periglischrus calcariflexus new species, was found on the Greater Long-tongued bat Leptonycteris nivalis (Saussure) in Mexico. The female, male, deutonymphs, and protonymph are described and illustrated. Additionally, we evaluate the morphological variability of this species based on its geographical distribution. Considering this new species, the number of species in the vargasi species group within the genus Periglischrus increases to five; therefore, herein we include a key for the known species in the vargasi species group for the Neotropics.